Evaluation of the Effect of Nano and Micro Hydroxyapatite Particles on the Impact Strength of Acrylic Resin: In Vitro Study - Ahmed Abdulameer Abduljabbar; Firas Abd kati; Ayad I. Haddad; Ihtesham Rehman (Journal of Techniques)
Poly (methylmethacrylate) is considered the basis material for a denture base. However, such substance has some drawbacks such as poor impact resistance, which is thought to be the primary cause of fracture of denture base resins. The purpose of the study was to determine how Nano and Micro hydroxyapatite particles affected the impact strength of acrylic resin. Thirty specimens were constructed of heat-cured acrylic resin and were divided into three groups: Ten specimens for the control, 10 for 1%nano hydroxyapatite, and 10 for micro hydroxyapatite. Acrylic samples were subjected to an impact strength test via a Charpy-type. Data were then analysed using SPSS v20.  The ANOVA test was used for comparison among the groups. Highly statistically significant differences among all studied groups (P-value <0.0001). Both 5% Micro hydroxyapatite and 1% Nano hydroxyapatite had a higher mean value than the control. Incorporating Nano and Micro hydroxyapatite into PMMA improved the impact strength of acrylic resins.